Pengembangan Media Pembelajaran Audiovisual Berbasis Aplikasi Prezi pada Materi Teks Biografi Kelas X SMK Swasta Kristen Tomosa 1 - Lince Imerda Gea; Mastawati Ndruru; Noveri Amal Jaya Harefa; Lestari Waruwu (Pusat riset dan Inovasi Nasional, 2025)
This study aims to develop and evaluate Prezi-based audiovisual learning media on biographical text material for class X students of SMK Swasta Kristen Tomosa 1. The development of this media uses the Research and Development (R&D) method with the ADDIE model which includes five stages: analysis, design, development, implementation, and evaluation. The results of the study indicate that Prezi-based audiovisual media has very good feasibility based on validation from three experts: material experts reaching (76.2%), language experts reaching (82.8%), and design experts reaching (85.7%). The practicality of the developed media is assessed through student response questionnaires in small group trials reaching (87%), which indicates that this media is very practical to use in learning. The effectiveness of the developed media is measured by the results of student learning tests, which show a percentage completion of 100% with an average score of 90, which meets the Learning Objective Achievement Criteria (KKTP). Based on these results, it can be concluded that Prezi-based audiovisual media is feasible, practical and effective to use for learning biographical text material at SMK Swasta Kristen Tomosa 1.